PENGELOLAAN KELAS INKLUSIF DI SEKOLAH DASARREGULER:Studi Kasus Terhadap Kegiatan Pengelolaan Kelas Inklusif di Sekolah DasarReguler dengan Anak Berkebutuhan Khusus - Deden Saepul Hidayat, - (2005)
The inclusive class management in regular elementary school (a case study to regular inclusive class management with children special needs). The result focused on how is the inclusive management in regular elementary school for children with special needs? The background of the research was the issue of the implementation of inclusive education in elementary school. The shift of paradigm of education of thought in inclusive education where all the children with special needs deserved to get the same opportunity with qualified education services. It implied two changes, first the change of education service in which the orientation was more to the need of the children; and second, the change of class management in public school where children with special needs went to. This research was done by qualitative and case study approach. The case of the research was a class where the children with special needs belonged. The classes were selected based on low class (first grade) and high class (fourth grade) in the same elementary school in Bandung. This selection based on looking for data variation. The result wasdone byinterview andobservation method. The results of the research were first understanding, inclusive education was comprehended by the teacher as open education, which was oriented in unifying the children with special need with the other children in the class. Second, class management planning should consider the special need of the children, the learning result, data and the input from daily discussion with special teachers or itenerant teacher, teacher, and parents. Third, the implementation of class management, teaching-learning process with various method, which were still classical and not yet optimum, concerned about individual need unless there was special attention to the children with special needs through learning individualization. The flexibility of material giving, learning media were adjusted to the need of the children. The collaboration between the supervisor and class management including class equipment was done naturally, but in the management of students' seats were done by the teachers with the consideration of student grouping and implementing peer tutoring and also the socialization of children with special needs to the whole class. The response to the class management, which was done by the teacher, was the attention to learn, play and interact among the student. Fourth, the evaluation should be planned with the consideration of the children with special need. The evaluation process was done by classical approach but the children with special needs were treated differently.